On Representing Syntactic Change: Towards a Theory of Diachronic Syntax - Matasović, Ranko (Array, 2004)
This paper discusses different approaches to diachronic syntax inherent in the difference between the functionalist syntactic theories (such as Role-and-Reference Grammar) and generative theories (such as Minimalism). It is shown that functionalist and generative theories make different predictions with respect to the possibility and relative frequency of particular syntactic changes, as well as with respect to the diachronic stability of certain syntactic features in linguistic families. Moreover, the Principle of Diachronic Stability, suggested by the author, predicts that semantically and pragmatically motivated syntactic features behave differently in the history of languages. This principle can be formulated only in a theory such as Role-and-Reference Grammar, which takes into account semantic and pragmatic factors that shape the syntax of a language.